Numerical study of base-isolated cylindrical liquid storage tanks using coupled acoustic-structural approach. Issue 119 (April 2019) - Rawat, Aruna; Matsagar, Vasant A.; Nagpal, A.K.
Abstract: A numerical study of the base-isolated ground-supported cylindrical liquid storage tank is carried out using finite element method (FEM). The coupled acoustic-structural (CAS) approach in the FEM is used for the analysis of the base-isolated tanks with rigid and flexible walls with varying parameters. Base isolation systems used in the present study are laminated rubber bearing (LRB) and friction pendulum system (FPS). The effects of aspect ratio (liquid height to radius) of the tank, and the isolation time period on the seismic response of the base-isolated tank is considered for investigation. For this study, the broad and slender tanks with three different isolation time periods are considered, which exhibit their relative flexibility. The sloshing displacement, base shear, hydrodynamic pressure, and bearing displacement responses are evaluated for three-dimensional (3-D) rigid and flexible tanks subjected to bi-directional components of earthquake ground motions. Moreover, the FE results are compared with the commonly used mechanical lumped-mass model of the base-isolated tank. The results show that as the time period of the isolator increases, i.e. increased flexibility, the base shear response is considerably reduced in both the rigid and flexible, broad and slender tanks. The reduction in the impulsive component causing base shear is more as compared to the convective (sloshing) component in the base-isolated tanks. The sloshing displacement increases with increase in the time period of the base isolation systems in both the rigid and flexible tanks. The impulsive hydrodynamic pressure along the tank wall is reduced with introduction of the isolation systems and the reduction is significantly more in case of the flexible isolators. The bearing displacement increases with increase in the time period of the isolation system adopted. Highlights: Finite element (FE)-based simulations using the coupled acoustic-structural (CAS) approach for fluid-structure interaction (FSI) in tank﻿. Sloshing, base shear, and hydrodynamic pressures induced in 3-D ground-supported cylindrical rigid and flexible base-isolated tanks. Bi-directional earthquake ground motion components affecting seismically base-isolated and non-isolated tanks.﻿